2016
DOI: 10.1016/j.cma.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Efficient implicit integration for finite-strain viscoplasticity with a nested multiplicative split

Abstract: An efficient and reliable stress computation algorithm is presented, which is based on implicit integration of the local evolution equations of multiplicative finite-strain plasticity/viscoplasticity. The algorithm is illustrated by an example involving a combined nonlinear isotropic/kinematic hardening; numerous backstress tensors are employed for a better description of the material behavior. The considered material model exhibits the so-called weak invariance under arbitrary isochoric changes of the referen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
(112 reference statements)
0
25
0
Order By: Relevance
“…Robust and efficient numerical procedures for the case where ψkin1 and ψkin2 are of neo‐Hookean type are presented in []. The case where ψkin1 and ψkin2 are of Mooney‐Rivlin type can be dealt with using an explicit update formula from [].…”
Section: Illustration Problem: Model With Combined Isotropic‐kinematimentioning
confidence: 99%
“…Robust and efficient numerical procedures for the case where ψkin1 and ψkin2 are of neo‐Hookean type are presented in []. The case where ψkin1 and ψkin2 are of Mooney‐Rivlin type can be dealt with using an explicit update formula from [].…”
Section: Illustration Problem: Model With Combined Isotropic‐kinematimentioning
confidence: 99%
“…In the special case of the flow rule (53) which corresponds to α = 0, the evolution equation governing C cr has the same structure as that for the model of multiplicative viscoplasticity proposed in [51]. An explicit update formula is described in [57] for this evolution equation; this explicit solution can be used for the presented creep model as well. As a result, the overall time stepping can be reduced to the solution of a single scalar equation (cf.…”
Section: Remarkmentioning
confidence: 99%
“…This decomposition allows one to incorporate evolving backstresses in a thermodynamically consistent way in different applications (see [23] for shape memory alloys, [7,11,28,49,51,61,67] for conventional plasticity and viscoplasticity, [22] for unconventional plasticity). Accurate and efficient numerical implementation of various models based on the nested multiplicative split was discussed, among others, in [20,46,51,57,67]. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Schüler et al 46 used the algorithm to model the viscoelastic behaviour of a bituminous binding agent. The closed-form solution reported by Shutov et al 42 is implemented as a part of efficient implicit procedures for finite-strain viscoplasticity 47 and finite strain creep. 24 In the current study, a new explicit update formula is suggested for a more general case of the Mooney-Rivlin hyperelasticity.…”
Section: Introductionmentioning
confidence: 99%